1022 Socioeconomic Deprivation and Colorectal Cancer Survival. (4th May 2021) - Ali, F; Jha, M
Abstract: Background: Factors related to CRC survival include age, tumour site and stage. Other factors that may play a role on survival include race and socioeconomic status(SES).We aim to investigate the impact of SES on CRC survival. Method: All patients diagnosed with CRC between January 2006-January 2019 were included. Demographics were collected from a prospective database. SES was defined using the Index of Multiple Deprivation(IMD).Cox-regression was used to investigate the effect of factors on survival and Kaplan-Meier to estimate survival. Results: A total of 5, 073 patients diagnosed with CRC with a median follow up of 65 months were include. Overall survival was 72.2% (76.0%0-78.4%), 59.6%(58.2%-61.0%) and 50.3% (48.8%-51.8%) at 1 year, 3 years and 5 years, respectively. Colon cancer was associated with worse survival(p = 0.00256, HR = 1.163). On multivariate analysis, socioeconomic deprivation was associated with poorer survival (HR = 1.02, p=0.00302).Male and female sex were associated with similar survival outcomes(HR = 0.9831 and 0.9341, respectively; p = 0.986 and 0.946 respectively). Conclusions: SES impact on CRC survival seems to be inconsistent across the literature potentially due to lack of uniformity of indices used to assess SES and the heterogeneity of access to healthcare. This could ultimately impact comparability across different studies investigating the impact SES on CRC survival.